Luputnya Kepentingan Penyandang Disabilitas Dalam Pembuatan Kebijakan Energi: Upaya Reformatif untuk Mencapai Energi yang Inklusif - Hasyim, M Fuad (Universitas Muhammadiyah Sumatera Utara, 2025)
Designing energy policies must consider aspects of social differences to create an inclusive society. This can be achieved by meeting the energy needs of each social class fairly and evenly. However, the experiences and needs of people with disabilities have not been a priority in energy policy making. People with disabilities often have less access to the energy sources they need. In addition, the energy needed by people with disabilities often does not match their needs. This article uses a capability approach to discuss the importance of considering people with disabilities in energy policy making and formulating an energy welfare framework for people with disabilities. Supported by a comprehensive literature study and critical reflection to collect, present, and interpret supporting data. This article produces three conclusions that support the creation of energy policies that support people with disabilities. First, it is important to know the barriers that limit the participation of people with disabilities in policy making. Second, these barriers can be overcome by reducing identity bias between people with disabilities and non-disabled people which can be done through a common ingroup identity framework. Third, by using a capability approach, policy makers must pay attention to what people with disabilities can do to support their lives without hindering their capacity. The author hopes that this article can be a step towards reforming more inclusive energy policies and that the energy rights of people with disabilities can be fulfilled evenly. Kata kunci: Disability; Energi; Policy; Inclusive